1999
DOI: 10.1103/physrevb.60.5963
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Al(100)-c(2×2)-Li: A binary surface alloy

Abstract: The atomic geometry of the Al͑100͒-c(2ϫ2)-Li phase formed by adsorption of 1 2 -ML Li on Al͑100͒ at room temperature has been determined by analysis of extensive low energy electron-diffraction ͑LEED͒ measurements. The structure is found to be a binary surface alloy, in which Li atoms occupy fourfold-coordinated substitutional sites formed by displacing every second Al atom in the first layer of the substrate. The surface structure is very similar to the ͑100͒ plane of the metastable, bulk Al 3 Li alloy. An an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
23
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 20 publications
4
23
1
Order By: Relevance
“…However, it has been an open question as to whether the surface structures have any relation to bulk Al-Li alloys. For the adsorption of Li on Al(100), it has been established that a c͑2 3 2͒-Li structure is formed in which 0.5 ML (monolayer) Li atoms substitute 0.5 ML Al atoms in the first layer [8]. This result has been confirmed by total-energy calculations in the present work and in a separate study [10].…”
supporting
confidence: 85%
See 1 more Smart Citation
“…However, it has been an open question as to whether the surface structures have any relation to bulk Al-Li alloys. For the adsorption of Li on Al(100), it has been established that a c͑2 3 2͒-Li structure is formed in which 0.5 ML (monolayer) Li atoms substitute 0.5 ML Al atoms in the first layer [8]. This result has been confirmed by total-energy calculations in the present work and in a separate study [10].…”
supporting
confidence: 85%
“…Previous studies have shown that submonolayer adsorption of Li on close-packed Al surfaces results in the formation of substitutional surface alloys [7][8][9]. However, it has been an open question as to whether the surface structures have any relation to bulk Al-Li alloys.…”
mentioning
confidence: 99%
“…AM adsorbates modify the substrate structure. Sometimes, rather significant structural changes such as noticeable reconstruction or surface alloy formation take place as reported for the cases of Li and Na on Al surfaces [1][2][3] and Li on Cu(1 0 0) surface [4]. In many cases, however, relatively small modifications such as surface relaxation and substrate rumpling have been reported [5] as found for example in the K/Ni(1 0 0)-c(4 · 2) [6], Na/ Ni(1 0 0)-c(2 · 2) [7], and Na/Cu(1 0 0)-c(2 · 2) surfaces [8].…”
Section: Introductionmentioning
confidence: 96%
“…The experimental results for the first interlayer distance range from +2.6% ͑LEED͒ to less than −2.5% ͑MeV IS͒, and several papers report 0% relaxation for this surface.. 2,[6][7][8][9][10][11][12][13][14] Only two experimental works give evidence of multilayer relaxations. 6,7 With LEED being the most common technique used to study relaxations, it is worth mentioning briefly how these results are obtained. This is achieved by analyzing the dependence of the intensity of selected beams on the energy of the incident electrons: the so-called I͑V͒ or I͑energy͒ curves.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the information about multilayer relaxations was not completely given in one work 7 and partially misinterpreted in the other. 6 Briefly, the experimental evidence of relaxations for the Al͑001͒ surface, besides the spread of the results, appears to be incomplete. In particular, no experimental work has considered the possibility of very deep relaxations.…”
Section: Introductionmentioning
confidence: 99%